Acarus immobilis Griffiths 1964 - Cilbircioğlu, Cihan; Çobanoğlu, Sultan (Zenodo, 2019)
{"references": ["Cobanoglu, S. (1996) Typhloctonus Muma, 1961 (Acarina: Phytoseiidae) species, from thrace of Turkey. Doga, Turk Tarim ve Ormancilik Dergisi, 20: 353 - 357.", "Cobanoglu, S. & Toros, S. (1988) \" Kasar peynirlerinde zararli akarlar \". Gida Dergisi, 13: 409 - 415.", "Solomon, M. E. (1962) Ecology of the flour mite, Acarus siro L. (= Tyroglyphus farinae DeG.). Annals of Applied Biology, 50 (1): 178 - 184.", "Solarz, K., Szilman, P. & Szilman, E. (1997) Preliminary study on the occurrence and species composition of astigmatic mites (Acari: Astigmata) in samples of dust, debris and residues from farming environments in Poland. Annals of Agricultural and Environmental Medicine, 4: 249 - 252.", "Mason, L. J. (2004) Grain mite Acarus siro (L.). Grain Insect Fact Sheet E- 222 - W. Department of Entomology, Purdue University. Available from: https: // extension. entm. purdue. edu / publications / E- 222 / E- 222. html (Accessed on 14. 01. 2019).", "Webster, L. M. I., Thomas, R. H. & McCormack, G. P. (2004) Molecular systematics of Acarus siro s. lat., a complex of stored food pests. Molecular Phylogenetics and Evolution, 32: 817 - 822."]}

Acarus immobilis Griffiths, 1964 Width: 266.25 ± 0.30 (221.91–317.42), length: 460.85 ± 0.38 (393.87–520.35) (n = 10). Specimens examined Taşköprü/ Centrum garlic storage, 7.VI.2014 (4 ♀♀, 4 ♂♂); Taşköprü/ Ağcıkişi Village. 10.IV.2015 (42 ♀♀, 23 ♂♂); Taşköprü Donalar Village garlic storage. 11.VII.2015 (4 ♀♀, 5 ♂♂). Comments Acarus immobilis was reported by Çobanoğlu (1996) on wheat in Edirne. The damage of this mite was also identified on kashar cheese by Çobanoğlu and Toros (1988). This mite is a polyphagous species, which is known as flour-cereal mite. Its hosts are flour, seed, onion, garlic, pet food, oilseed, harvested grain, hay, grass, soils, medicinal plants, cheese, abandoned beehives, deep poultry (Solomon 1962; Solarz et al. 1997; Mason 2004; Webster et al. 2004). In this study, it was found on head, green parts and storage of garlic cultivation areas in six villages of Taşköprü.

Published as part of Cilbircioğlu, Cihan & Çobanoğlu, Sultan, 2019, Phytophagous mite (Acari) species on garlic (Allium sativum L.) cultivation areas and storages of Kastamonu, Turkey, pp. 211-224 in Persian Journal of Acarology 8 (3) on page 218, DOI: 10.22073/pja.v8i3.46349, http://zenodo.org/record/7173998
Keywords: Arthropoda; Acarus immobilis; Arachnida; Animalia; Acarus; Biodiversity; Sarcoptiformes; Taxonomy; Acaridae; 3. Good health